Mitochondrial DNA as a tool for identification of genetic diversity among domestic animals - Budimir, Kristina; Jovanovac, Sonja; Mijić, Pero; Margeta, Vladimir (Acta Agraria Kaposváriensis, 2014)
Mitochondrial DNA (mtDNA) is genetic marker that is often used in population and evolutionary biology. The best preserved part of the D-loop is its central part while other segments are subject to change. Busha is autochthonous breed of cattle that is bred extensively on the territory of Republic Croatia. During the last century there has been significant reduction in her size which has led to an endangerment of the breed. Busha is the part of cultural heritage and valuable gene source, which is the one of the reasons for its preservations. Research was conducted on 15 samples of Busha. Samples were collected on five different locations on territory of Croatia. Research was carried out on the most variable part of mtDNA (D-loop). The results of the research revealed the variability in the mtDNA D-loop sequences. The most common substitutions within the D-loop were C/T and A/G substitutions. Degree of genetic divergence within population is nearly 27%. The aim of this paper was to examine efficiency of mtDNA as a molecular marker in the analysis of genetic diversity among animal population. In this research we have used population of busha.